1996
DOI: 10.1111/j.1432-1033.1996.0494u.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Capillary Endothelial Cells Express two forms of Erythropoietin Receptor mRNA

Abstract: To study the existence of the erythropoietin receptor (Epo-R) mRNA in brain capillary endothelial cells, the reverse transcription (RT) PCR was performed using total RNAs from rat brain capillary endothelial cells (RBECs) and MBEC4, which is one of the established mouse brain capillary endothelial cell lines. Southern analysis of the RT-PCR products indicated that both RBECs and MBEC4 expressed an authentic form of Epo-R mRNA as a minor form and an intron-5-inserted form of Epo-R mRNA, thus a soluble form of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
147
0
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(158 citation statements)
references
References 41 publications
4
147
0
7
Order By: Relevance
“…28 EPO-R have also been identified on human and rodent umbilical vein and brain capillary endothelial cells, where in vitro studies on rats suggest that EPO may play an important role in angiogenesis 15,16,29,30 and act as a vascular competence factor. 17 Angiogenic effects of rHuEPO have also been demonstrated on rat cardiomyocytes 19 and aortic tissue. 30 EPO and other hematopoietic cytokines may regulate the differentiation of neurons in the brain, 31 and a neurotrophic role of EPO has been postulated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…28 EPO-R have also been identified on human and rodent umbilical vein and brain capillary endothelial cells, where in vitro studies on rats suggest that EPO may play an important role in angiogenesis 15,16,29,30 and act as a vascular competence factor. 17 Angiogenic effects of rHuEPO have also been demonstrated on rat cardiomyocytes 19 and aortic tissue. 30 EPO and other hematopoietic cytokines may regulate the differentiation of neurons in the brain, 31 and a neurotrophic role of EPO has been postulated.…”
Section: Discussionmentioning
confidence: 98%
“…EPO and EPO-R have been identified on nonerythroid cell lines, and important nonerythropoietic functions for this cytokine growth hormone have been proposed. In vitro human and animal research has demonstrated the functional presence of EPO and EPO-R on endothelial cells, [15][16][17] placental cells, 18 cardiomyocytes, 19 and in the central nervous system. 6,7,20 -26 The presence of EPO and EPO-R in neural cell lines of postimplantation mouse embryos suggests a role in embryogenesis and neurogenesis as well as in hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…EpoR mRNA is expressed in endothelial cells from various sources (Anagnostou et al, 1994;Yamaji et al, 1996). Epo stimulates proliferation and migration of endothelial cells (Anagnostou et al, 1990) and also in vitro angiogenesis (Carlini et al, 1995).…”
mentioning
confidence: 99%
“…EpoR mRNA is expressed in endothelial cells from human umbilical vein, bovine adrenal capillary, and rat brain capillary (28,29). Epo stimulates proliferation and migration of human and bovine endothelial cells (30) and also angiogenesis of the rat thoracic aorta (31).…”
mentioning
confidence: 99%